Study on Different Hormones and Feed Additives Used for Cattle Fattening in Mymensingh District (Journal of Environmental Science and Natural Resources, 2017)
To develop a database on growth promoters and feed additives in cattle fattening a purposive survey was carried out. It is done among 30 cattle fattening farmers covering 1 Upazilla under 3 union in Mymensingh district of Bangladesh, who were involved in cattle fattening activities before Eid-Ul-Azha (August to November2015). The survey was done covering farmers information, livestock population and production system, feed sources, manpower involvement, availability, types of hormones, feed additives use with negative opinion and probable suggestions for controlling whereas the researcher had no control or could not manipulate the variables as the appeared. All the farmers interviewed during the survey period were literates, and about 52% of them had primary education, 27% had secondary school certificates, 14% obtained higher secondary certificate and the rest were graduates and post-graduates, 7%. Irrespective of literacy about 10% of the interviewed farmer had training on cattle fattening and the rest fattened cattle without having any sort of training. About 35% respondents use skilled personal for cattle fattening. In the study areas, most of the farmers (55%) were using roughage and 45% of them use concentrate. The fattened cattle were marketed by farmers is 98% and rest 2% by butcher or others. About 72% of the farmer use Tracoll and 28% use Ketofox as feed additives and as hormone 30% farmers use Betamethasone, 55% use Decasone and 15% use Periactin. In public perception 89% farmers use growth promoters in wrong period and 80% use harmful feed additives, feeding natural feed in low amount is (65%). Consumers are less concern to buy fattened bull (93%). The mean of the suggestions like veterinary services (1.26), doses in proper ages (2.06), feeding balanced feed (1.62), organic growth promoters program (0.60) and knowledge through ICT program (0.03). From the above results it may be concluded that, major number of cattle are fattened by small farmers in the survey area. For this fattening purpose different types of hormones and feed additives available in the market are used by them. It can be concluded that, the percentages of different negative opinions on using hormones and feed additives is higher.J. Environ. Sci. & Natural Resources, 9(2): 109-113 2016